Caring for patients with a congenital heart defect: a national survey of the educational needs of nurses. (29th July 2021) - Griffiths, L; Seaton, S; Lotto, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Around 1 in every 130 babies are born with a structural heart defect. Over the past half century, advances in treatment have resulted in increasing numbers surviving with complex disease. Currently, around 90% survive into adult life. In order for these patients to receive a high standard of care throughout their lifespan, it is imperative that nurses are educated appropriately. This is supported by the NHS England Standards (2016), which provides recommendations on minimum staffing levels, but also demands that staff are competent to deliver that care. Aims: The aim of this study was to explore the educational needs of nurses who may encounter this group of patients. Methods: A national online survey was undertaken between 4/06/2020 to 06/07/2020. Results: A total of 513 individual survey responses were received from both paediatric and adult nurses and AHPs (representative of an all age service), working in all levels of care. Regardless of where the nurse worked, band 5 nurses reported a higher level of anxiety about caring for patients with congenital heart disease (CHD) in comparison to the whole cohort (18% versus 12%). In the previous two years, 30% of the band 5 staff had received no training. Of the band 5s who had received no training, 71% were based in non-CHD settings. Both band 5 nurses and staff of all grades working in non-CHD centres identified managing emergencies (band 5: 77% and non-CHD: 76%), caring for a patient with CHD (band 5: 71% and non-CHD: 72%) and a simple understanding of CHD (band 5: 61% and non-CHD: 67%) as priority topics. Whilst the majority of band 5, and non-CHD centre nurses who had received recent education had undergone a local study day (band 5: 33% and non-CHD: 34%) or self-directed learning (band 5: 38% and non-CHD: 31%), formal or accredited courses were rated most desirable (band 5: 93 and non-CHD: 84%). Conclusion Whilst education within specialist level 1 and 2 centres appears to be well developed and embedded, junior nurses (band 5) and particularly those working in non-cardiac units, appear to be being left behind. Easy access information pertaining to emergency care, alongside simple descriptions of care requirements would benefit those nurses who rarely encounter CHD patients. Digital and other innovative approaches may work well as memory aids and provide a solution alongside formal training. Consideration to including fundamentals of care within the nursing curriculum would potentially provide a base from which nurses can develop. Preferences for accredited, formal study sessions support the need for further development of post graduate education.